Ultrasonic Degradation of Fuchsin Basic in Aqueous Solution: Effects of Operating Parameters and Additives - Rui-Jia Lan; Ji-Tai Li; Bao-Hua Chen (International Journal of Photoenergy)
Ultrasonic degradation is one of the recent advanced oxidation processes (AOPs) and proven to be effective for removing low-concentration organic pollutants from aqueous solutions. In this study, removal of fuchsin basic from aqueous solutions by ultrasound was investigated. The effects of operating parameters such as ultrasound power (200 W–500 W), initial pH (3–6.5), and temperature (15, 22, 35, and 60°C) on the ultrasonic degradation were studied. The degradation of fuchsin under ultrasound irradiation basic was found to obey pseudo first-order reaction kinetics. Addition of catalyst Fe(II) had a markedly positive effect on degradation. 84.1% extent of degradation was achieved at initial dye concentration 10 μmol L−1, ultrasound power 400 W, ultrasound frequency 25 kHz, dosage of Fe(II) 4 mg L−1, initial pH 6.5, and temperature 22°C. But addition of heterogeneous catalyst TiO2 affected degradation slightly. Addition of radical scavenger suppressed fuchsin basic degradation significantly.